TNF-α (G-308A) Polymorphism, Circulating Levels of TNF-α and IGF-1: Risk Factors for Ischemic Stroke—An Updated Meta-Analysis - Duan, Ranran; Wang, Na; Shang, Yanan; Li, Hengfen; Liu, Qian; Li, Li; Zhao, Xiaofeng (Frontiers in Aging Neuroscience, 2022)
Objective:Accumulated studies have explored gene polymorphisms，circulating levels of TNF-α and IGF-1 in the etiology of Ischemic stroke (IS). Of the numerous etiopathological factors for IS, a single-nucleotide polymorphisms (SNPs) rs1800629 located in the TNF-α gene promoter region and increased levels of TNF-α were found to be associated with IS in different ethnic backgrounds. However, the published results are inconsistent and inconclusive. The primary objective of this meta-analysis was to investigate the concordance between rs1800629 polymorphism and IS. As secondary aims we explore circulating levels of TNF-α and IGF-1 with IS in different ethnic background，differentially sourced specimens. Methods:In this study, we examined whether rs1800629 genetic variants, levels of TNF-α and IGF-1 were related to the etiology of IS by performing a meta-analysis. Relevant case-control studies were retrieved by database searching and systematically selected according to established inclusion criteria. Results:47 articles were identified that explored the relationship between the rs1800629 polymorphism, levels of the TNF-α and IGF-1 with IS risk susceptibility. Statistical analyses revealed a significant association between the rs1800629 polymorphism, levels of TNF-α and IGF-1 with IS pathogenesis. Conclusion:Our findings demonstrated that the TNF-α rs1800629 polymorphisms, the increased levels of TNF-α and decreased IGF-1 were involved in the etiology of IS.